2019
DOI: 10.1177/1938640019826701
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes After Fracture-Dislocation of the Ankle

Abstract: Background. Fracture dislocation of the ankle represents a substantial injury to the bony and soft tissue structures of the ankle. There has been only limited reporting of functional outcome of ankle fracture-dislocations. This study aimed to compare functional outcome after open reduction internal fixation in ankle fractures with and without dislocation. Methods. A retrospective chart review of surgically treated ankle fractures over a 3- year period was performed. Demographic data, type of fracture, operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Few studies have reported medium- or long-term results in fracture-dislocation of the ankle [ 9 , 11 , 12 , 16 ]. Warner et al [ 9 ] compared short-term functional outcomes in pronation external rotation ankle fractures with and without dislocation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Few studies have reported medium- or long-term results in fracture-dislocation of the ankle [ 9 , 11 , 12 , 16 ]. Warner et al [ 9 ] compared short-term functional outcomes in pronation external rotation ankle fractures with and without dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…All our patients had a fracture-dislocation of the ankle, in some cases caused by low energy trauma, especially in elderly patients. Tantigate et al [ 12 ] reported a retrospective study of 118 patients surgically treated for an ankle fracture; 33 patients (28%) sustained a fracture-dislocation. After a medium followup of 37 months, 62 patients were analyzed for functional outcome assessed by the Foot and Ankle Outcome Score (FAOS).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations